Modern french songs george to widor for high voice - HALE, Philip (Oliver Ditson co., 1904)
Georges alexandre, Gavotte of the masqueradenGodard, Benjamin..Remembrance, Come and embark, LovenGounod, Charles.. To spring, Medje, The valley